2022
DOI: 10.57267/jisym.v11i2.110
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Berhubungan Dengan Pemberian ASI Eksklusif Pada BayiDi Wilayah Kerja Puskesmas Huraba Kabupaten Tapanuli Selatan

Abstract: Exclusive breastfeeding is that babies are only breastfed for six months without additional fluids and other foods except medicated syrup. The coverage of exclusive breastfeeding in Indonesia in 2018 of 65.16% has not reached the national target (80%), the coverage of exclusive breastfeeding in working area of Puskesmas Huraba in Tapanuli Selatan Regency in 2019 is around 23.2%. This study aims to determine the factors associated with exclusive breastfeeding in infants in Puskesmas Huraba, Tapanuli Selatan Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Respondents with positive (supportive) social culture tend to exclusively breastfeed their babies. This statement is supported by one study which found that mothers with socio-cultural support in breastfeeding have six times the opportunity to exclusively breastfeed, analogous to those with unsupportive socio-cultures [24].…”
Section: Discussionmentioning
confidence: 88%
“…Respondents with positive (supportive) social culture tend to exclusively breastfeed their babies. This statement is supported by one study which found that mothers with socio-cultural support in breastfeeding have six times the opportunity to exclusively breastfeed, analogous to those with unsupportive socio-cultures [24].…”
Section: Discussionmentioning
confidence: 88%